Short-term financing sources in Africa: Substitutes or complements? - Machokoto, Michael; Mahonye, Nyasha; Makate, Marshall (Elsevier, 2021)
Using panel vector autocorrelation models (Panel VaR), we examine the dynamic interrelationships between short-term financing sources for a large sample of 8,464 firm-year observations from seven understudied developing economies over the period 1991-2015. On average, we find that short-term debt and trade credit are complements, while cash holdings are substitutes for short-term debt and trade credit. However, our further analyses show that the interrelationships between short-term financing sources are strong and significant before the financial crisis but diminish thereafter with contractions in credit supply. These changes highlight the impact of credit supply shocks on short-term financing policies of firms domiciled in less-developed capital markets. As firms in Africa, an exemplary less-developed capital market context, rely heavily on short-term financing sources, the dynamic interrelationships we document have important implications that are of interest to academics, practitioners, and policymakers alike.